Women in peacebuilding: A criticism of gendered solutions in postconflict situations - Erzurum, Kemal; Eren, Berna (Routledge, 2014)
Women are the most suffering part of populations in conflicts. They are required to fulfill different responsibilities during and after conflicts. Considering this fact, participation of women at peacebuilding efforts in postconflict areas has been considered as sine qua non requirement. However, active participation of women at these efforts, particularly decision-making activities, has been hampered due to diverse reasons. The barriers that block women involved in peacebuilding processes as decision-makers should be reexamined and eliminated by eradicating inequalities. In this article, gender-based violence, underestimated plight of women in conflicts, gendered approach of peacebuilding efforts, and the barriers in front of women's active participation in decision-making processes are examined.
Keywords: Conflict; Decision Making; Gender; Peace; Peacebuilding; Women